Evaluation of the impacts of photodynamic therapy on the prognosis of patients with hrHPV infection based on BTNL8 expression - Lv, Hongqing; Lou, Shuai; Zhang, Lin; Cui, Dawei; Li, Yao; Yang, Ying; Chen, Meilan; Chen, Pan (Frontiers in Oncology, 2023)
Objective The aim of this study was to evaluate the prognostic value of Butyrophilin-like protein 8 (BTNL8) expression in high-risk HPV (hrHPV) infection treated with photodynamic therapy. Methods A total of 93 patients with hrHPV infection were enrolled as research study subjects, along with 69 healthy women who served as controls. Serum samples were obtained from each participant, and BTNL8 levels were quantified. The patients were divided into high- and low-expression groups (n = 45 and n = 48, respectively), and both groups underwent photodynamic therapy. We recorded the following data: BTNL8 expression pre-treatment and at 3/6 months post-treatment, HPV negative conversion ratio, regression rate of low-grade squamous intraepithelial lesions (LSIL), incidence of adverse reactions, complication rate, serum inflammatory factors, persistence of HPV positivity, LSIL residue or recurrence, and incidence of high-grade cervical intraepithelial lesions (HCIL). Results Patients with HPV infection exhibited higher BTNL8 expression than healthy individuals. Compared to the low-expression group, the high-expression group showed increased HPV negative conversion ratios, LSIL regression rates, and levels of IL-17 and IL-23. This group also demonstrated decreased total complication rate, HPV positivity persistence, LSIL residue or recurrence, and IL-10 levels. Additionally, there was no significant difference between the two groups in terms of the number of adverse reactions and cases with LSIL residue/recurrence. Conclusion Serum BTNL8 expression may serve as a valuable tool for early screening and prognosis monitoring of patients with hrHPV infection.